The Effect of Workload, Burnout, and Job Satisfaction on Turnover Intention in General Practitioners in Indonesia - Amelia Wijaya, Lisa (Publikasi Indonesia, 2025)
Turnover intention is the desire to move or leave the job. High turnover intention can harm hospitals and disrupt the quality of patient service. Several factors affect turnover intention, namely individual, group, and company factors. This study was conducted to determine the effect of workload, burnout, and job satisfaction on turnover intention in general practitioners in Indonesia. This research was conducted online involving 188 general practitioner respondents who work as clinicians in hospitals and clinics throughout Indonesia. Data collection was carried out by distributing a questionnaire containing 29 questions with a Likert Scale of 1 – 5 based on the purposive sampling method. The results of filling out the questionnaire will be analyzed by the partial least square-structural equation modeling (PLS-SEM) method. The results of this study stated that workload and burnout had a positive influence and job satisfaction had a significant negative influence on turnover intention in general practitioners working in hospitals/clinics. Therefore, management must pay attention to the workload and burnout rate as well as the job satisfaction of general practitioners to prevent turnover intention.